Pengaruh media ceramah, leaflet dan vcd dalam pencegahan gangguan akibat kekurangan iodium - Feby A Metekohy, Toto Sudargo dan Fatwa Sari Tetra Dewi (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Iodine Deficiency Disorder (1DD) is still one among nutritional problems in Indonesia. Primary School teachers are the target group of health promotion for IDD control in the education institution because the general impact of IDD toward the primary school students could cause mental retardation and the declining of intelligence level until 10 points below their abilities. The total of Goiter Rate (TGR) of Maluku Province tends to increased. Objectives: This research was aimed at finding out the influence of speech with media of VCD and leaflet through health promotion toward teacher in the effort of IDD prevention among Primary School's students. Methods: This study was quasi experimental with pretest and posttest control group design. The sample was sport and health education teacher (Penjaskes) in the sub district of Amahai and Teon Nila Serua (TNS). It was chosen purposively. Data was taken by using questionnaire. Crosscheck of student's knowledge was also implemented in order to find out teacher's practice. Analysis was using statistical test of paired t-test and t-test for difference test with significance level of p = 0,05. Results: There was a significant influence of a health promotion regarding 1DD toward the improvement of knowledge, attitude and teacher's practice. There was a more significant improvement in the intervention group than control group. There was also a significant improvement on knowledge of primary school children regarding IDD. Conclusion: Speech method that is supported by leaflet and VCD could improve knowledge, attitude and practice of teacher through health promotion regarding IDD as well as it could improve knowledge of students regarding IDD through teacher's practice.Keywords: IDD, Primary School student, Central Maluku